2015
DOI: 10.1155/2015/603859
|View full text |Cite
|
Sign up to set email alerts
|

Simple Lymphangioma to Generalized Lymphatic Anomaly: Role of Imaging in Disclosure of a Rare and Morbid Disease

Abstract: Generalized lymphatic anomaly is a rare multisystem congenital disorder in which multiple organs are involved. Imaging features often overlap with other complex lymphatic anomalies and diagnosis is difficult. Treatment options are limited, not remedial and prognosis is poor. We report a 12-year-old male who presented with axillary and chest wall lymphangioma but was subsequently diagnosed as having diffuse lymphangiomatosis affecting lungs, liver, spleen, and bones on computerized tomography scan. We suggest c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 11 publications
1
8
0
4
Order By: Relevance
“…Existe conteúdo gasoso em permeio à coleção situada à direita, Cutillo et al descreveram que a linfangiomatose também pode envolver outras vísceras abdominais e o retroperitônio. 12 A biópsia com análise anatomopatológica continua sendo a ferramenta de diagnóstico definitivo; [1][2][3][4][5][6][7][8] entretanto, estabelece como possível diagnóstico preciso o caso com sintomatologia, derrames quilosos e padrão radiográfico compatível. 13 Não existe abordagem terapêutica padrão.…”
Section: Resultado Dos Principais Exames Complementaresunclassified
See 2 more Smart Citations
“…Existe conteúdo gasoso em permeio à coleção situada à direita, Cutillo et al descreveram que a linfangiomatose também pode envolver outras vísceras abdominais e o retroperitônio. 12 A biópsia com análise anatomopatológica continua sendo a ferramenta de diagnóstico definitivo; [1][2][3][4][5][6][7][8] entretanto, estabelece como possível diagnóstico preciso o caso com sintomatologia, derrames quilosos e padrão radiográfico compatível. 13 Não existe abordagem terapêutica padrão.…”
Section: Resultado Dos Principais Exames Complementaresunclassified
“…13 Não existe abordagem terapêutica padrão. 3,10 Por vezes, a mesma visa paliativamente 6 reduzir os sintomas, visto a ausência de cura para a síndrome. Entre as opções já consideradas se tem: transfusão de albumina, dietas de triglicerídeos de cadeia média com baixo teor de gordura, interferon alfa, corticosteroides, tamoxifeno, bisfosfonatos, imatinib, talidomida, ciclofosfamida, acetato de medroxiprogesterona, octreotide, vincristina e ligação do ducto torácico para o quilotórax, 8,14,15 porém, até o momento sem resultados promissores e com efeitos adversos importantes.…”
Section: Resultado Dos Principais Exames Complementaresunclassified
See 1 more Smart Citation
“…Liver cysts and/or chylothorax were reported in only 5 cases, but were invariably lethal. [ 1 7 17 22 25 ] Spleen involvement has also been reported in GLA [9] …”
Section: Discussion and Reviewmentioning
confidence: 99%
“…As these cells are lymphatic, some authors have suggested that this disorder should be called “generalized lymphatic abnormality” (GLA) rather than “cystic angiomatosis” (CA), [ 8 9 ] particularly as tissues other than bone may be affected. However, although GLA does indeed commonly affect bone, this condition is often both congenital and fatal [10] .…”
Section: Introductionmentioning
confidence: 99%